The Floodplain Forests of the Mamberamo Basin, Papua, Indonesia (Western New Guinea): Vegetation, Soils, and Local Use - Sheil, D.; Boissière, M.; Heist, M. van; Rachman, I.; Basuki, I.; Wan, M.; Watopa, Y. (MDPI, 2021)
New Guinea is the world’s largest, most speciose, and most culturally rich tropical island, and the little-studied Mamberamo Basin of Papua (Indonesian New Guinea) is recognised among the region’s most-important areas for biological diversity. Here, we examined the floodplain forests in the indigenous territory of Papasena, within the Mamberamo-Foja Wildlife Reserve in the Mamberamo Basin. As part of a training activity with local researchers, students, and civil servants, and with the permission and assistance of the local people, we employed various methods including the field surveys detailed here. We used variable-area tree plots, transects for non-trees and soil sampling, and local informants to document 17 plots: four in old-growth dryland forest, five in old-growth swamp forests (two seasonally flooded and three permanently wet including one dominated by sago, Metroxylon sagu Rottb.), five in secondary forest (fallows), and three in gardens (two in swamps and one on dryland). In total, we measured 475 trees over 10 cm in diameter at 1.3 m (dbh). The swamp forests had high local basal areas (highest value 45.1 m2 ha−1) but relatively low statures (20 m but with emergent trees over 40 m). In total, 422 morphospecies from 247 genera and 89 different families were distinguished. These included 138 tree species and 284 non-tree plant species. A quarter (105) of the morphospecies lacked species-level identifications. The woody families Rubiaceae, Araceae, Moraceae, and Euphorbiaceae were especially diverse, with 20 or more morphospecies each. Tree richness was highest in dryland forest (plot 7 having 28 species in 40 stems over 10 cm dbh) with more variation in the flooded forests. Non-tree vegetation showed similar patterns ranging from 65 species in one 40-by-5 m primary forest plot to just 5 in one seasonally flooded forest plot. The local people identified many plants as useful. Among trees, at least 59 species were useful for construction (the most common use), while, for non-trees, medicinal uses were most frequent. Inceptisols dominated (12 plots), followed by Ultisols and Entisols (3 and 2 plots, respectively). Drainage appeared poor and nutrient availability low, while land-suitability criteria implied little potential for crops aside from sago. We discuss the implication of local practises and more recent developments that may threaten the conservation of these floodplain systems. We underline the key role of local people in the oversight and protection of these ecosystems.